2019
DOI: 10.3390/jrfm12010022
|View full text |Cite
|
Sign up to set email alerts
|

Does the Misery Index Influence a U.S. President’s Political Re-Election Prospects?

Abstract: We seek to determine whether a United States President’s job approval rating is influenced by the Misery Index. This hypothesis is examined in two ways. First, we employ a nonlinear model that includes several macroeconomic variables: the current account deficit, exchange rate, unemployment, inflation, and mortgage rates. Second, we employ probit and logit regression models to calculate the probabilities of U.S. Presidents’ approval ratings to the Misery Index. The results suggest that Layton’s model does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Işık & Çetenak (2019) ampirik olmayan çalışmasında BRICS ülkeleri ve Türkiye'yi sefalet endeksi açısından tablo ve grafikler yardımıyla karşılaştırmış ve yeterli bir endeks değerine sahip olmadığı sonucuna ulaşmıştır. Adrangi & Macri (2019) Sefalet endeksindeki değişimler ile ABD başkanlarının yeniden seçilmesi arasında bir ilişki tespit etmiştir.…”
Section: Literatür öZetiunclassified
“…Işık & Çetenak (2019) ampirik olmayan çalışmasında BRICS ülkeleri ve Türkiye'yi sefalet endeksi açısından tablo ve grafikler yardımıyla karşılaştırmış ve yeterli bir endeks değerine sahip olmadığı sonucuna ulaşmıştır. Adrangi & Macri (2019) Sefalet endeksindeki değişimler ile ABD başkanlarının yeniden seçilmesi arasında bir ilişki tespit etmiştir.…”
Section: Literatür öZetiunclassified
“…Tang and Lean (2009) concluded that there was a positive relationship between the misery index and growth of crime in the USA during the period 1960-2005. The influence of the MI on the US presidential performance was investigated by Adrangi and Macri (2019) using macroeconomic variables, and they concluded that the misery index has a significant impact on the US presidential performance. To summarize, we conclude that the misery index has a greater impact on the growth of a country.…”
Section: Misery Index and Economic Growthmentioning
confidence: 99%
“…Over time, the MI has seen various applications; for example, Cakici and Zaremba (2023) found that the misery index is a reliable predictor of cross-sectional stock returns. For their part, Adrangi and Macri (2019) found that the MI has a statistically significant effect on the probability of approval of U.S. presidents' performances. Meanwhile, Dadgar and Nazari (2018) found the existence of a negative relationship between economic growth and MI; they also found a statistically significant relationship between the index and government type.…”
Section: Introductionmentioning
confidence: 99%